2018
DOI: 10.1021/acs.jpcc.8b03680
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Isotopic Effects on a Surfactant Headgroup at the Air–Liquid Interface

Abstract: The geometry, arrangement, and orientation of a quaternary ammonium surfactant flanked by two methyl groups, a benzyl head, and an octyl tail were assessed at the air–water and air-deuterium oxide (D2O) interfaces using sum frequency generation vibrational spectroscopy. Remarkably, symmetric and asymmetric N–CH3 stretches (at ∼2979 and ∼3045 cm–1, respectively, in the SSP polarization combination) were visible in water but negligible in deuterium oxide. We concluded that D2O addition triggers the average reori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 66 publications
1
29
0
Order By: Relevance
“…SFG is a submonolayer surface/interface sensitive second-order nonlinear optical spectroscopy. , In a typical SFG experiment, two input beams, a visible beam with a fixed frequency and a frequency tunable mid-IR beam, overlap on a sample in time and in space, generating a signal beam with the sum frequency of the two input beams. The SFG process can be considered as a combined infrared absorption and antistokes Raman scattering process.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SFG is a submonolayer surface/interface sensitive second-order nonlinear optical spectroscopy. , In a typical SFG experiment, two input beams, a visible beam with a fixed frequency and a frequency tunable mid-IR beam, overlap on a sample in time and in space, generating a signal beam with the sum frequency of the two input beams. The SFG process can be considered as a combined infrared absorption and antistokes Raman scattering process.…”
Section: Methodsmentioning
confidence: 99%
“…It is challenging to probe polymer–biological molecule interactions because such interactions occur at solid/liquid interfaces. Sum frequency generation vibrational spectroscopy (SFG) is a second-order nonlinear optical spectroscopic technique with submonolayer surface/interface selectivity, which can be applied to study molecular structures of many buried interfaces including solid/liquid interfaces. ,,, We have extensively applied SFG to investigate detailed structural information on interfacial biological molecules, such as proteins and peptides, while interacting with various materials , including polymers. ,, SFG can probe the amide I signals from interfacial peptides and proteins using different polarizations of the beams and determine their orientations. Interfacial ordering and time-dependent structural changes of biological molecules on polymer surfaces have also been examined using SFG. , In addition, we applied SFG to study polymer surface changes after protein absorption, focusing on methyl groups …”
Section: Introductionmentioning
confidence: 99%
“…SFG vibrational spectroscopy (or SFG in short) is a second-order nonlinear optical technique which is submonolayer surface sensitive because of its special selection rule: under the electric dipole approximation, SFG signal can only be generated from a medium with no inversion symmetry. SFG probes the macroscopic second-order nonlinear susceptibility χ (2) of a material, while χ (2) is nonzero only for a sample with no inversion symmetry. , Most bulk media are centrosymmetric, thus do not have SFG signal, while surfaces and interfaces lack inversion symmetry and can generate SFG signals. For a charged interface like silica–water interface, it is believed and shown that there are bulk (3) contributions from the electric double layer/diffuse layer near the silica–water interface.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Here we studied nonionic surfactants and water at the silica–surfactant solution interface. SFG is a surface-specific second-order nonlinear optical spectroscopy probing second-order nonlinear susceptibility χ (2) of a medium, which has been developed into a powerful tool to investigate surfaces and interfaces. We have applied SFG to study a variety of complex surfaces and interfaces including biological molecules, polymers, as well as surfactants. , The silica–water interfaces have been extensively studied by SFG in various aspects. Silanol groups on a silica surface can be deprotonated in an aqueous solution under neutral pH (SiOH ⇄ SiO – + H + ), which results in a negatively charged silica surface in contact with water. , Different surface structures of silica can form different types of hydrogen bonding with water at the buried silica–water interface, making water molecules ordered at the immediate silica–water interface (the nearest water layer on silica), which contribute to SFG signals. …”
Section: Introductionmentioning
confidence: 99%
“…Sum frequency generation (SFG) vibrational spectroscopy is a second-order nonlinear optical technique with intrinsic interface sensitivity. SFG has been extensively employed to study molecular structures of solid/liquid interfaces. We have demonstrated that the valuable molecular information for polymer/solution interfaces obtained by SFG can contribute to the elucidation of interfacial behaviors of polymer, water, and biological molecules. , To gain fundamental understandings of the interfacial behaviors in CFRP, SFG was applied to characterize the molecular structures of carbon fiber/sizing solution and plastic/sizing solution interfaces in this study.…”
Section: Introductionmentioning
confidence: 99%